1989
DOI: 10.5860/crl_50_01_42
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Profile of "College & Research Libraries"

Abstract: Recent trends in authorship and referencing practices in the pages of College & Research Libraries are studied. A dramatic increase in the use of quantitative techniques, beginning around 1970 and peaking in the period 1980-84, is also demonstrated. s the Association of College and Research Libraries celebrates its fiftieth anniversary, an examination of the past accomplishments of the association is in order. This examination would be incomplete without an analysis and appreciation of the role that College & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…A study of authors' citing practices in College & Research Libraries over a long time-span showed a very similar pattern of increase in references per paper (Metz, 1989). It is noteworthy that there were considerably more citations per paper, on average, in JASIS than in College & Research Libraries during the years of overlap of the Metz study and the present study.…”
Section: References In Jasis Paperssupporting
confidence: 72%
See 2 more Smart Citations
“…A study of authors' citing practices in College & Research Libraries over a long time-span showed a very similar pattern of increase in references per paper (Metz, 1989). It is noteworthy that there were considerably more citations per paper, on average, in JASIS than in College & Research Libraries during the years of overlap of the Metz study and the present study.…”
Section: References In Jasis Paperssupporting
confidence: 72%
“…A trend toward greater participation by female authors has been observed in the literatures of various disciplines, including the literature of librarianship (e.g., Olsgaard & Olsgaard, 1980;Metz, 1989;Buttlar, 1991). The field of information science, as represented by JASIS, also shows this trend toward increased female participation (Fig.…”
Section: Author Gendermentioning
confidence: 76%
See 1 more Smart Citation
“…For example, in a statistical profile of College & Research Libraries (C&RL) on its fiftieth anniversary, Paul Metz described C&RL as "one of the most widely respected journals in librarianship,'' noting that ARL directors and library school deans ranked it first and third, respectively, in terms of "its value for tenure and promotion decisions at their institutions. '' 4 A ''self-fulfilling prophecy" occurs because, once publicized, these subjective rankings influence assessment of the best outlet for a journal article and the subsequent weight assigned to it in personnel deci- • 5 s1ons. This author recalls a comment made at a discussion group on negotiating the tenure process held at an Association for Library and Information Science Education conference: "If it's not published in one of the top ten or twelve journals listed in the Kohl and Davis study, it doesn't count as much."…”
mentioning
confidence: 99%
“…In his statistical profile of C&RL, Paul Metz found that articles appearing in recent issues of the journal used quantitative methodologies more frequently, especially for the display of information, when compared to articles appearing in previous decades. 13 Suhasini Kumar examined 312 articles from ten LIS journals, including JAL. 14 Specifically, Kumar studied subject mat-…”
mentioning
confidence: 99%